2020
DOI: 10.1186/s12877-020-1427-1
|View full text |Cite
|
Sign up to set email alerts
|

Mobile device use and the cognitive function and depressive symptoms of older adults living in residential care homes

Abstract: Background: With the fast-paced aging and increasing digitalization of society, there has been a growing interest in the effect of mobile device use on cognitive function and depression in older adults. However, research examining this issue among older adults in residential care homes (RCHs) is scant. Therefore, this study aimed to examine the impact of mobile device use on the cognitive function and depressive symptoms of older adults living in RCHs. Methods: A cross-sectional survey was conducted using a so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…First, the most potent predictor of cognitive function in the young-old group was electronic device-based activities, which is in line with previous findings that older adults who use mobile devices demonstrate better cognitive functions [ 33 ] and that owning a computer or cell phone slows down the rate of cognitive decline [ 34 ]. A study that analyzed the predictors of cognitive function in older adults [ 35 ] also reported that electronic device-based activities were the strongest predictor of cognitive function in older adults.…”
Section: Discussionsupporting
confidence: 84%
“…First, the most potent predictor of cognitive function in the young-old group was electronic device-based activities, which is in line with previous findings that older adults who use mobile devices demonstrate better cognitive functions [ 33 ] and that owning a computer or cell phone slows down the rate of cognitive decline [ 34 ]. A study that analyzed the predictors of cognitive function in older adults [ 35 ] also reported that electronic device-based activities were the strongest predictor of cognitive function in older adults.…”
Section: Discussionsupporting
confidence: 84%
“…The lack of significant change in depressive symptoms for the smartphone-based videoconferencing group corresponds with the smartphone study of Tsai et al. 18 Although NH residents who are regular users of mobile devices such as smartphones have been shown to have lower levels of depressive symptoms than non-users, 32 the failure to detect a reduction in depressive symptoms might be due to the NH residents’ lack of familiarity with a smartphone.…”
Section: Discussionsupporting
confidence: 74%
“…A 2016 survey in Xiamen in China showed 30% of adults aged 60+ years used smartphones, and more functions were positively associated with increased general and partial subdomain cognitive functions [ 10 ]. Another small-scale, cross-sectional survey in China showed association between the usage of mobile phone and cognitive function [ 11 ]. Since social contact and intellectual activities were both identified as protective factors of cognitive impairment [ 8 , 12 ], the mobile phone users may have better cognitive function due to minimized social isolation and enhanced cognitive skills.…”
Section: Introductionmentioning
confidence: 99%